The Magnificat: Cento, Psalm or Imitatio? - Simons, Robert (2009)
Scholars have long noted the prominence of LXX words and themes in the Magnificat (Luke 1.46-55). Various attempts have been made to explain this prominence. Some have suggested that the Magnificat is a sort of cento, others that it is modelled upon the OT Psalms. This study will propose that it is an example of what was known in the Graeco-Roman rhetorical tradition as speech in character (προσωποποιΐα) employing the technique of imitatio, and will show that many details in the text of the hymn seem to support this hypothesis.
Keywords: Cento; Rhetoric; Imitatio; magnificat; luke; Synoptic Gospels; Gospels; New Testament